(untitled) (Raparin Journal of Humanities (RJH), 2021)
The study aims to explain and identify the trends of the Kurdish media elite with regard to the level of commitment of Kurdish websites to professional ethics in the Kurdistan Region. This study is a descriptive study in which the survey method was used. The community of this study is consists of the media elite in the Kurdistan Region, whether it is the lecturers in the media departments in the universities and institutes of the region, or the experienced media professionals who are in charge of managing media institutions. The most prominent results of the study are: The majority of the study sample agrees that the content of Kurdish websites is a mixture of adherence to the principles of professional ethics, especially in presenting all the information related to the event and avoiding intentional exaggeration, and also non-compliance with these principles, especially in their lack of commitment to the sources of information contained in the news.